Effects of civil society on urban planning and governance in Mysore, India - Sadashiva, Manjunath (Technische Universität Dortmund, 2008)
The current global policy on urban governance in the cities of the third world seeks to harness associational forms of civil society as an interface for civic engagement and an instrument to achieve efficiency in service delivery. This normative and undifferentiated treatment of civil society has not only led to a wide spread scholarly debate on the very concept of civil society but also to the emergence of alternative radical and transformatory paradigms about state-civil society relations. Set in this backdrop, the thesis evolves a conceptual framework, develops research tools, and applies them in Mysore, a South Indian city, in pursuit of empirical evidence on the nature of civil society and the effects they induce on various spheres of urban planning and governance. In this regard, collective empowerment of individuals, changes in the institutional arrangements, and the outcomes of decision making processes are identified as the possible effects of associational civil society and are, therefore, used as dependent variables. On the other hand, the organizational attributes of civil society, the political opportunity structures, mobilization of social structures and the struggle over symbolic capital (for e.g. shaping public opinion) in the public sphere are conceptualized as determinants of the effects of civil society. The study reveals that the associational terrain of urban governance in Mysore is highly differentiated in terms of organizational attributes, ethnic composition, the degree of political orientation, functional domains and spatial levels. The state and the civil society are shown as sharing a mutually influential and inseparable relationship. The study generates ample empirical evidence to conclude that associational forms of civil society do induce effects on the level of collective empowerment of individuals, the public sphere and the institutions of urban planning and governance in the city of Mysore. These effects are depicted as outcomes of the complex interplay between various factors such as the differential organizational features of associations; socio-economic attributes of their constituents; their ability to organize and mobilize social structures; the strategies they use to influence public opinion in the public sphere; and finally the state’s response to their actions. The study also uncovers the potential of associational civil society to enhance rationality of urban planning in Mysore.
Keywords: Civil society; Urban planning; Mysore; Governance; Empowerment; India; Zivilgesellschaft; Stadtplanung; Mysore; Indien; Staatsführung; Vollmacht; 710